Endocrine abnormalities in townes–brocks syndrome. Issue 9 (25th July 2013) - Lawrence, Cara; Hong‐McAtee, Irene; Hall, Bryan; Hartsfield, James; Rutherford, Andrew; Bonilla, Tracy; Bay, Carolyn
Abstract: Townes–Brocks syndrome is a recognizable variable pattern of malformation caused by mutations to the SALL1 gene located on chromosome 16q12.1. Only three known cases of Townes–Brocks syndrome with proven SALL1 gene mutation and concurrent endocrine abnormalities have been previously documented to our knowledge [Kohlhase et al., 1999; Botzenhart et al., 2005; Choi et al., 2010]. We report on two unrelated patients with Townes–Brocks syndrome who share an identical SALL1 mutation (c.3414_3415delAT), who also have endocrine abnormalities. Patient 1 appears to be the first known case of growth hormone deficiency, and Patient 2 extends the number of documented mutation cases with hypothyroidism to four. We suspect endocrine abnormalities, particularly treatable deficiencies, may be an underappreciated component to Townes–Brocks syndrome. © 2013 Wiley Periodicals, Inc.